Acute coronary syndrome- A vulnerable patient with vulnerable plaques: A case report - Antonio Maglione; Salvatore Ambrosio; Carmina Campaniello; Sandro Nello; Raffaele Papa (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2019)
Acute coronary syndromes (ACS) are the most frequent cause of hospitalization in western countries and may be complicated by acute heart failure or sudden cardiac death. The underlying mechanism of ACS is plaque rupture, endothelial erosion, and/or intraplaque haemorrhage with partial or complete occlusion of an epicardial coronary artery. Vulnerable plaques are characterized by increased inflammatory infiltrates circulating inflammatory biomarkers of vulnerable plaques have been identified. They provide valuable diagnostic and prognostic information. However, they do not provide insight in the anatomic localization of vulnerable plaques. Intravascular ultrasound (IVUS) can provide detailed, high-quality tomographic images of coronary plaque and identify unstable plaque. We describe a case report of a vulnerable patient with two vulnerable plaques, with antero-inferior ST elevation acute coronary syndrome.